Experimental investigation and Optimization of FSW on Eglin Steel. Issue 1 (December 2020) - Paulmar Pushparaj, J; Jeremiah, R; Prabhakaran, D; Shankaranarayanan, S; David, D; Billy, D; Giridharan, K
Abstract: Friction Stir Welding (FSW) is belongs to the solid state welding process. The welding joints were completed by compressive force which can be achieved through the rotational speed of pin. In this process, the welded material was operated below the recrystallization temperature. The heat was formed due to frictional force between the pin and work piece. This experimental investigations have been provided to address the FSW of eglin steel. The Ultimate Tensile Strength (UTS) was the output of the experiment which it was depends on the input factor such as welding speed, feed and pin rotational speed. Taguchi optimization was performed to found the optimal factor. The variance analysis was used to found the contribution factor.